Understanding the effect of surface finish on stress corrosion crack initiation in warm-forged stainless steel 304L in high-temperature water. (15th April 2019) - Chang, Litao; Burke, M. Grace; Scenini, Fabio
Abstract: Surface machining is often assumed to be detrimental to stress corrosion cracking (SCC) in nuclear power plant components because of localized deformation, high associated hardness, roughness and tensile residual stresses. However, in the present work, SCC initiation studies for a warm-forged Type 304L stainless steel in high-temperature water showed that the 1–2 μm thick ultrafine-grained layer introduced by machining improved SCC initiation resistance. Removing the macroscopic machining ridges via grinding decreased the residual tensile stress but led to more extensive cracking. This paradigm shift demonstrates the dominant effect of the microstructure on the oxidation over the mechanical driving force for SCC. Graphical abstract: Unlabelled Image